Exploring translation strategies for Singapore based ecoculture essays - Xu, Fei (Nanyang Technological University, 2023)
The strategies of foreignization and domestication have been much discussed in cultural-related translation. Translation strategies applicable to ecoculture articles that contain both cultural and ecological content, however, have been rarely addressed. This project produces the Chinese translation for two such Singapore-based ecocultural essays and explores the translation strategies applied. An integrated approach of translation has been taken involving both foreignization and domestication, justified with examples. While foreignization serves to exoticize articles and arouse the reader’s interest, domestication provides a smooth reading experience to promote environmental sustainability among a larger readership in the greater Mandarin Chinese-speaking circle.